2016
DOI: 10.1007/s11356-016-7126-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary unsaponifiable fraction of extra virgin olive oil supplementation attenuates lung injury and DNA damage of rats co-exposed to aluminum and acrylamide

Abstract: Aluminum chloride (AlCl3) and acrylamide (ACR) are well known as environmental pollutants inducing oxidative stress. Our study investigated the effects of these contaminants and if the hydrophilic fraction of extra virgin olive oil was able to prevent lung oxidative stress and DNA damage. Animals were divided into four groups of six each: group 1, serving as controls, received distilled water; group 2 received in drinking water aluminum chloride (50 mg/ kg body weight) and by gavage acrylamide (20 mg/kg body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 71 publications
(73 reference statements)
4
6
0
Order By: Relevance
“…It was found that the antioxidant activity of GSH, SOD and GST decreased after using AS at a low dose and that the inhibition of the antioxidant activity increased after using a high dose of AS due to the accumulation of free radicals that led to membrane fragility. This finding is in accordance with other authors' results [9,[28][29][30][31]. In our study, treating the models with the natural product, propolis extract, along with low and high doses of AS displayed an ameliorative response of the cellular antioxidant activity.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…It was found that the antioxidant activity of GSH, SOD and GST decreased after using AS at a low dose and that the inhibition of the antioxidant activity increased after using a high dose of AS due to the accumulation of free radicals that led to membrane fragility. This finding is in accordance with other authors' results [9,[28][29][30][31]. In our study, treating the models with the natural product, propolis extract, along with low and high doses of AS displayed an ameliorative response of the cellular antioxidant activity.…”
Section: Discussionsupporting
confidence: 94%
“…In the histopathological investigation, it was noticed that the rat lungs treated with a low dose of AS showed some blood vessel hemorrhage and numerous inflammatory granulated and non-granulated cells, such as neutrophils, alveolar macrophages and lymphocytes. At a high-dose of AS, it caused eosinophilia, the formation of hyaline casts inside the cores of lung bronchioles, edema, numerous lymphocytes, neutrophils, inflammatory granular cells, the appearance of fibroblastic spread, the accumulation of macrophages replacing lung tissues and the hemorrhage of blood vessels that pass through the pulmonary alveoli [29,30]. In previous studies, the evaluation of the action of silica on lung tissue was compatible with our results for the cytotoxicity of aluminum silicate [35,36].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In vivo studies in rodent models showed that ACR treatment caused increased ROS production in serum, lung and brain (Ghorbel et al, 2016;Lakshmi et al, 2012;Zhang et al, 2013). Our study also found that ACR-treated zebrafish embryos had a significant increase in ROS production (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…It has also been shown to have anti-inflammatory, antithrombotic, antihypertensive and vasodilatory effects in both animals and humans (14). The possible mechanism explaining the beneficial role of EVOO may be due to its contents of monounsaturated fatty acids (MUFA) essentially oleic acid and polyphenols as reported by our previous studies (15,16). Data assessing the health effects of EVOO used as a dietary supplement after acrylamide treatment are lacking.…”
Section: Introductionmentioning
confidence: 96%